Key meliacins and nutrients in different neem-cakes - KUMAR, JITENDRA; PAL, MADAN; PARMAR, B S (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted during 1999-2000 to estimate the meliacins content, crude proteins, total sugars as well as Ca and Fe content of the laboratory-processed and market purchased neem-cakes. Different solvents (methanol, ethanol, dichloromethane, ethyl acetate etc) were tried to remove the meliacins present in neem-cake to reduce its toxicity. The cakes obtained after extraction of the seeds with methanollmd aqueous methanol recorded nil or negligible contents ofmeliacins. In laboratory-processed cakes, total sugars, protein, calcium and iron contents ranged from 1.1 to 2.9%, 25.54 to 33.21 %, 3.65 to 13.5 ppm and 14.02 to 27.35 ppm respectively.